Highly stable Saccharomyces cerevisiae L-BC capsids with versatile packing potential - Celitan, Enrika; Stanevičienė, Ramunė; Servienė, Elena; Serva, Saulius (Frontiers in Bioengineering and Biotechnology, 2024)
Virus-like particles (VLPs) are promising nanoscaffolds in development of vaccines and nanodelivery systems. Along with efficient production in various expression systems, they also offer extensive functionalization options. Nevertheless, the ultimate integrity of VLPs is an important burden for the applicability in nanobiotechnology. In this study, we characterize the Saccharomyces cerevisiae L-BC VLPs synthesized and purified from Escherichia coli and Saccharomyces cerevisiae cells. The particles exhibited prominent size stability in buffers within a range of ionic strength conditions, pH environment and presence of magnesium ions during the long-term storage at temperatures up to 37°C. Bacteria-derived particles exhibited alleviated stability in acidic pH values, higher ionic strength and temperature compared to yeast-derived particles. Taking advantage of gene engineering, 120 copies of red fluorescent protein mCherry were successfully encapsulated into both preparations of L-BC VLPs, while passive diffusion enabled encapsulation of antimicrobial peptide nisin into the yeast-derived unmodified VLPs. Our findings indicate that L-BC VLPs generally exhibit high long-term stability under various conditions, while yeast-derived L-BC VLPs are more stable under the elevated temperatures than bacteria-derived particles. Stability studies and encapsulation of particles by different molecules involving alternative strategies delineate the L-BC VLP potential to be developed into versatile nanodelivery system.